Fool's gold [videorecording (DVD)] - Tennant, Andy, 1955-; McConaughey, Matthew, 1969-; Hudson, Kate, 1979-; Sutherland, Donald, 1935- (Warner Home Video, 2008)
Finn is looking for a lost Spanish galleon in the Caribbean. He believes he has found the galleon and has marked the location with his own sunken boat. He enlists the help of his ex-wife, Tess, who is intrigued until she finds he has no real proof of the Spanish ship's location. Fate has put the two together again, this time onboard the boat of multi-millionaire Nigel Honeycutt and his daughter, Gemma. Nigel is fascinated by Finn's story and wants to help him find the treasure. Moe is an old mentor of Finn's who also happens to be looking for the same treasure. Watching both is gangster rapper Bigg Bunny who Finn owes money to. Finn and Tess discover a clue as to where the fortune may lie. Now all Finn has to do is get the gold, get the girl, and get going before Bigg Bunny gets him.